Genetic variation and population status of sharks: A comparative mtDNA study in the waters of Aceh Jaya and West Aceh - Burhanis Burhanis; Samsul Bahri; Derila Erima (Universitas Malikussaleh, 2025)
Mitochondrial DNA (mtDNA)-based genetic analysis is important for revealing evolutionary relationships, supporting taxonomy, and providing a basis for conservation management. This study was conducted in the waters of Aceh Jaya and West Aceh, two regions with high shark fishing activity but minimal genetic data. A total of 12 shark individuals (6 per location) were collected from fish landing ports, then dorsal muscle tissue was taken, preserved in ethanol, and analyzed using DNA extraction, sequencing, and bioinformatics methods. Molecular identification through comparison with GenBank showed a very high level of similarity (Query Cover 99–100%, Identity 100%), with detected species including Carcharhinus falciformis, Sphyrna lewini, and Hemigaleus microstoma, reflecting a wide distribution in the western waters of Aceh. The nucleotide composition showed a dominance of thymine bases and a higher A+T ratio than G+C, consistent with the characteristics of shark genomes. Phylogenetic analysis showed a monophyletic clade with strong bootstrap support (100%) and placed S. lewini as the earliest differentiated taxon. Our results confirm the efficacy of DNA barcoding for accurate species identification and genetic diversity mapping, while underscoring urgent conservation concerns, as most species identified are classified as Vulnerable to Critically Endangered on the IUCN Red List. Keywords: Aceh; DNA Barcoding; Genetic Variation; Phylogenetics; Sharks